Marco Polo opera within an opera - Tan, Dun 1957- (Opus Arte, 2009)
In 'Marco Polo, an opera within an opera', composer Tan Dun portrays the Venetian explorer's travels to the Far East as a journey of both inner and physical discovery, a voyage depicting spiritual experiences as well as a geographical expedition. At the same time the work, on a libretto by Paul Griffiths, can be seen as a compositional adventure of the composer himself, unifying the various cultural worlds he occupies: a blend of Western avant garde and Oriental traditions